1997
DOI: 10.3168/jds.s0022-0302(97)76193-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Restraint Using Self-Locking Stanchions on Dairy Cows in Relation to Behavior, Feed Intake, Physiological Parameters, Health, and Milk Yield

Abstract: Holstein cows (n = 64) ranging from peak to end lactation were restrained in self-locking stanchions (i.e., head locks) for approximately 4 h/d for four periods in a modified switchback design. Milk yield, milk fat percentage, somatic cell count, and dry matter intake and dry matter intake were unaffected by restraint. Milk protein percentage was significantly lower for cows that were restrained. Plasma cortisol concentrations and the ratio of neutrophils to mononuclear cells were not significantly different b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 5 publications
1
24
1
3
Order By: Relevance
“…The expected effect of this housing system on the performance of the animals, with regard to cross-breeding, is minimal for the analysed traits. Milk production does not differ in a loose housing systems compared with stanchion housing system (Heizer et al, 1953;Bolinger et al, 1997), and no effects were shown of locking up the cows on udder health (Bolinger et al, 1997). The cows still exhibit oestrus symptoms such as hyperemia, swelling of vulva, discharge of cervical mucus and bellowing (Takagi et al, 2005), and therefore, no effect on fertility is expected either.…”
Section: Discussionmentioning
confidence: 94%
“…The expected effect of this housing system on the performance of the animals, with regard to cross-breeding, is minimal for the analysed traits. Milk production does not differ in a loose housing systems compared with stanchion housing system (Heizer et al, 1953;Bolinger et al, 1997), and no effects were shown of locking up the cows on udder health (Bolinger et al, 1997). The cows still exhibit oestrus symptoms such as hyperemia, swelling of vulva, discharge of cervical mucus and bellowing (Takagi et al, 2005), and therefore, no effect on fertility is expected either.…”
Section: Discussionmentioning
confidence: 94%
“…Os resultados foram inferiores aos encontrados por Agenäs et al (2003), os quais submeteram 12 vacas primíparas a um período de 48 horas de privação total de alimento, e obtiveram 66% de redução na produção de leite. Entretanto, os resultados deste trabalho foram superiores aos encontrados por Bolinger et al (1997), que mantiveram 64 vacas Holandesas presas sem alimentação, durante quatro horas por dia, em períodos de sete dias, e não encontraram diferença na produção de leite. Provavelmente, na restrição executada por Tabela 2.…”
Section: Resultsunclassified
“…Bolinger et al (1997), as vacas compensaram a falta temporária de alimento com aumento do consumo nas horas de maior disponibilidade. Neste trabalho, os animais foram mantidos confinados, sem compensação do consumo em outro momento.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Depriving lactating dairy cows of opportunities for both feeding and lying will help to determine their priorities for these two behaviours. Bolinger et al (1997) found that although postdeprivation feeding frequency was reduced after 4 h deprivation of lying and feeding when cows were placed in restraint yokes, feed intake and milk yield were not affected. Plasma cortisol, neutrophil-to-mononuclear cells ratio and somatic cell count (SCC) were not affected by restraint, but grooming and agonistic behaviours were increased and there was increased lying post restraint.…”
Section: Introductionmentioning
confidence: 90%